Determinasi Kepemimpinan Transformasional, Etos Kerja, Komitmen Organisasional, dan Motivasi Kerja Terhadap Kinerja Guru SMA Negeri di Kota Denpasar - M.D. Risadiana; A.A.G. Agung; I.M. Yudana (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to 1) determine the magnitude of the determination of transformational leadership on the performance of public high school teachers in Denpasar city, 2) determine the magnitude of the determination of work ethic on the performance of state high school teachers in Denpasar city, 3) determine the magnitude of the determination of organizational commitment on the performance of state high school teachers in the city Denpasar, 4) knowing the magnitude of the determination of work motivation on the performance of public high school teachers in the city of Denpasar, 5) knowing the magnitude of the simultaneous determination of transformational leadership, work ethic, organizational commitment, and work motivation on the performance of teachers of public high schools in the city of Denpasar. This research is an "ex-post facto" study with a sample size of 233 people. Data is collected with questionnaires and documents. Data analysis was performed using simple regression, multiple regression, and partial correlation techniques. The results of the study show that: (1) there is a significant determination between transformational leadership on the performance of public high school teachers in Denpasar City, with a correlation coefficient of 0.433 and an effective contribution of 9.01%. (2) there is a significant determination between the work ethic on the performance of public high school teachers in Denpasar City, with a correlation coefficient of 0.314 and an effective contribution of 4.71%. (3) there is a significant determination between organizational commitment to the performance of public high school teachers in Denpasar City, with a correlation coefficient of 0.255 and an effective contribution of 0.38%. (4) there is a significant determination between work motivation on the performance of public high school teachers in Denpasar City, with a correlation coefficient of 0.513 and an effective contribution of 19.01% (5) together, there is a significant determination between transformational leadership, work ethic , organizational commitment and work motivation on the performance of public high school teachers in Denpasar City, with a multiple correlation coefficient of 0.575 and a determination of 33.17% on the performance of public high school teachers in Denpasar City.